Web-age information management : 15th International Conference, WAIM 2014, Macau, China, June 16-18, 2014. Proceedings - Li, Guoliang; Hwang, Seung-won; Yao, Bin; Zhang, Zhenjie; Li, Feifei (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 15th International Conference on Web-Age Information Management, WAIM 2014, held in Macau, China, in June 2014. The 48 revised full papers presented together with 35 short papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on information retrieval; recommender systems; query processing and optimization; data mining; data and information quality; information extraction; mobile and pervasive computing; stream, time-series; security and privacy; semantic web; cloud computing; new hardware; crowdsourcing; social computing.